Autoimmune Pancreatitis: A Report from India - Noor, Mohd T; Lal, Anupam; Kochhar, Rakesh; Singhal, Manphool; Sidhu, Gurbakshish S; Srinivasan, Radhika; Rawat, Amit; Dutta, Usha; Dhiman, Radha K; Chawla, Yogesh K; et al. (JOP. Journal of the Pancreas, 2010)
Context Autoimmune pancreatitis is characterized by immune-mediated inflammation, prominent lymphocytic infiltration and fibrosis of pancreas. It accounts for 4.6-6% of chronic pancreatitis but only a few cases from India have been reported. Objective Evaluation of cases of autoimmune pancreatitis diagnosed between July 2006 and June 2009. Design Retrospective analysis of the clinical records of all patients diagnosed as autoimmune pancreatitis between July 2006 and June 2009. Setting Tertiary care centre, northern India. Main outcome measure Clinical records of all patients with autoimmune pancreatitis were analyzed with respect to their initial diagnosis and treatment, imaging, cytology, serology, presence of other organ involvement and response to treatment. Results The 5 cases of autoimmune pancreatitis included 4 men and one woman ranging in age from 48 to 60 years. The interval between initial consultation and diagnosis ranged from 3 months to 7 years. Symptoms included obstructive jaundice (5/5), abdominal pain (3/5) and weight loss (3/5). In 3 cases a presumptive diagnosis of a pancreatic mass with a biliary stricture was made and, in one patient, the diagnosis of primary sclerosing cholangitis was considered. These four patients had received a biliary stent and it was only on follow-up and review of the repeat CT scan that a diagnosis of autoimmune pancreatitis was suggested. In one patient, a diagnosis of autoimmune pancreatitis was considered in the first instance. Radiologically, all 5 patients showed a bulky pancreas with loss of lobulations. Conclusion In this report from India, we highlight the need for a high index of suspicion in diagnosing autoimmune pancreatitis because it responds dramatically to steroids. Image: Pancreatic acinar cell cluster with lymphocytes and plasma cells in the background.